Importance of Indicators of Nitroxidergic System in Improving the Treatment of Acute and Chronic Purulent Sinusitis - G'ayrat Umrullayevich Lutfullayev; Dilshod Shodiyevich Fayzullayev (International Journal on Human-Computing Studies, 2023)
In this article, an understanding of sinusitis, a topic relevant in today's medicine, is given, and detailed information is also given about their treatment methods. In addition, examples of new treatment measures are provided.